KARAKTERISTIK TEMPAT BERKEMBANGBIAK NYAMUK DAN STATUS RESISTENSI LARVA Aedes TERHADAP INSEKTISIDA ORGANOFOSFAT DI DESA PANGGUNGHARJO DAN BANGUNHARJO, KECAMATAN SEWON, KABUPATEN BANTUL, DAERAH ISTIMEWA YOGYAKARTA - , DEFRIANA LUTFI CHUSNAIFAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Dengue Haemorragic Fever, transmitted by Aedes mosquito (female) that spread almost in around the world. Aedes lived cosmopolite and it is breed in wet environment. Panggungharjo and Bangunharjo Village are an endemic and nonendemic area of DBD. To control the mosquito population is using insecticides which can result in the occurrence of organofosfat resistance in Aedes mosquitoes so it should be constantly monitored. The purpose of this research is to study how is the characteristic of the mosquito Aedes breeding place, what species that can be founded and how is the status of the mosquito Aedes larvae resistance against insecticides organofosfat associated with esterase enzyme activity in the Panggungharjo and Bangunharjo, Sewon, Bantul, DI Yogyakarta. The methods used in this research is a survey that conducted at 200 houses in Panggungharjo and Bangunharjo. Larvae resistance test using the biochemics method. Characteristics of mosquitoâs breeding place are an open-aired container, filled with clear and calm water, dark and rough wall suface, the bottom surface is undirectly contact with soil, waterâs temperature are 25-29 Â° C, pH 6-8, and not exposed directly by the sunlight. Only one species of mosquito was found, the Aedes aegypti. Aedes larvae resistance test shows that the status of the larvae of Aedes in Panggungharjo Village are susceptible and Bangunharjo Village are resistance.